2004
DOI: 10.1080/00016480310000755a
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of low-frequency hearing in cochlear implantation

Abstract: This study reports successful conservation of hearing after cochlear implantation using a modified surgical technique. Even high levels of hearing could be maintained, showing that implantation of an intracochlear electrode can be performed atraumatically with preservation of functional structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
2
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(225 citation statements)
references
References 14 publications
8
198
2
16
Order By: Relevance
“…If frequencies with no responses were present at the maximum output of the audiometer, then the maximum output plus 5 dB was entered to avoid losing data. This approach was used previously by Balkany et al and Kiefer et al (19,20).…”
Section: Audiometric Assessmentmentioning
confidence: 99%
“…If frequencies with no responses were present at the maximum output of the audiometer, then the maximum output plus 5 dB was entered to avoid losing data. This approach was used previously by Balkany et al and Kiefer et al (19,20).…”
Section: Audiometric Assessmentmentioning
confidence: 99%
“…Preserving inner ear function has been achieved through modification of electrode designs (Gantz and Turner 2004;Lenarz et al 2006;Gstoettner et al 2008;Fraysse et al 2006), the adoption of new surgical techniques (Lehnhardt 1993;Briggs et al 2005;Kiefer et al 2004), and more recently through the use of pharmacological treatments to the inner ear in the peri-operative period. Hearing protection can be achieved in experimental animals undergoing cochlear implantation when glucocorticosteroids are applied to the inner ear Eastwood et al 2010a, b;James et al 2008;Maini et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of these individuals suffer from progressive hearing loss that is most severe in the basal cochlea. The specific needs of this group has led to the development of cochlear implant devices designed to stimulate the high frequency region of the cochlea while maintaining mid and low frequency acoustic function (Kiefer et al, 2004;James et al, 2005;Lenarz et al, 2006) and limited clinical trials of these devices have been reported (Turner et al, 2004;Gantz et al, 2005;Kiefer et al, 2005;Gantz et al, 2006;James et al, 2006). Animal studies will be invaluable in understanding how electrical and acoustic signals interact in the cochlea and central nervous system and how to minimize perceptual distortions resulting from these interactions through changes in signal processing and/or electrode array design (von Ilberg et al, 1999;Nourski et al, 2005;Vollmer, 2006, personal communication).…”
Section: Future Directionsmentioning
confidence: 99%